Estudo dos impactos das intervenções da construção civil no meio ambiente: o caso do bairro Coroa do Meio em Aracaju/SE - Vasconcelos, Luciano Silva (2017)
The construction industry currently answers for a large part of the negative impacts of human actions, either by consumption of inputs and raw materials or by conflicts with these human interventions in urban space. As one of the activities that most impacts society, generating benefits or drawbacks, it has a direct influence on environmental, social, economic and a city or area landscape. This paper aims to map the impacts of construction on major transformations in the landscape of a neighborhood called Coroa do Meio in the city of Aracaju/SE, from 1976 to 2017. The research has a quantitative, qualitative and exploratory approach on a case of study. The methodological procedures were divided into two phases, the first was a literature review and the second was subdivided into four stages: the first stage was named object, which was held literature, historical and geographical survey of the case of study, the Coroa do Meio neighborhood; the second stage comprises the application of ad-hoc method with structured interviews about environmental impact in the study area, with transcription of speech and detection of key words through AntConc 3.4.3 software; the third stage comprises the production of maps of the area in 1976, 1978, 1984, 2003, 2008, 2010, 2013 and 2016, using maps or satellite images of the study area in the mentioned periods using the Quantum Gis 2:14.3 software, adopting Overlay mapping as a method; finally the fourth stage processes the results data of stages two and three, analyzing the interviews by respondent and analyzing the superposition of maps between the years mentioned in stage three. Therefore, the research identified that the environmental impacts generated by civil construction transformed and continue to transform the natural environment of Coroa do Meio initiated with large landfills of natural landscapes. The advance of human occupation is the most serious impact, since human activities from civil construction continue to deteriorate the small percentage of natural landscape still existing in the neighborhood area. Finally, this paper provides subsidies to support studies for development of innovative action plans and solutions, allowing the elimination of negative impacts or its mitigation